2011
DOI: 10.1007/s10029-011-0887-9
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency and safety of mesh fixation in laparoscopic inguinal hernia repair using n-butyl cyanoacrylate: long-term biocompatibility in over 1,300 mesh fixations

Abstract: IntroductionIn adult patients, most inguinal hernias are treated by implanting a prosthetic mesh. To prevent mesh dislocation and thus recurrence, different types of fixation have been proposed. In contrast to penetrating fixation known to cause acute chronic pain, adhesive fixation is becoming increasingly popular as it reduces markedly the risk of injury and chronic pain. Apart from the biological sealants (e.g., fibrin glue), surgical adhesives include a group of synthetic glues and genetically engineered p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
58
0
10

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(71 citation statements)
references
References 28 publications
(18 reference statements)
0
58
0
10
Order By: Relevance
“…[22,50] Besides, their use for the obliteration of processus vaginalis during hydrocelectomy has been also reported. [9][10][11][12] Their use with mesh In an experimental trial, Kukleta et al [13] performed mesh fixation in rabbits with CA glue -nBCA (Histoacryl ® ), and did not observe a reaction in muscle tissue during the acute phase. They reported fibroblastic tissue reaction characterized by mildly or moderately inflammatory cells.…”
Section: Priapismmentioning
confidence: 99%
See 2 more Smart Citations
“…[22,50] Besides, their use for the obliteration of processus vaginalis during hydrocelectomy has been also reported. [9][10][11][12] Their use with mesh In an experimental trial, Kukleta et al [13] performed mesh fixation in rabbits with CA glue -nBCA (Histoacryl ® ), and did not observe a reaction in muscle tissue during the acute phase. They reported fibroblastic tissue reaction characterized by mildly or moderately inflammatory cells.…”
Section: Priapismmentioning
confidence: 99%
“…Their study demonstrated suitability of using tissue adhesives as the first alternative based on comparative assessments of benefit, and economic burden. [13] Application of cyanoacrylate tissue adhesives Devices are available for superficial, vesical, intraureteral, intraurethral, tissue, intravascular, and laparoscopic applications. Figure 4 shows shows application devices.…”
Section: Priapismmentioning
confidence: 99%
See 1 more Smart Citation
“…The fourth technique (cyanoacrylate repair) is not currently reported in literature, although cyanoacrylate has been used extensively in other fields of surgery 27,37,38 . The repair of a cartilage flap using fibrin glue is ideal, since it is fast, relatively inexpensive and can be carried out arthroscopically 12,15 .…”
Section: Discussionmentioning
confidence: 98%
“…Orthopaedic research with cyanoacrylates is limited to skin closure, tendon and meniscal repair 42e44 . The safety of Glubran 2™ for internal use has been extensively reported in gastrointestinal surgery 27,38 , so far however, there are no reports in the literature describing its use for chondral repair. Nbutyl-2-cyanoacrylate is a liquid compound that polymerizes rapidly in the presence of hydroxyl ions.…”
Section: Discussionmentioning
confidence: 98%